The Effect of Education using Comics on the Knowledge of Earthquake Mitigation of 4th Grade Students at Al-Azhar 16 Islamic Elementary School Cilacap - Reza, Anggit; Wijaya, Oktomi; Qomariyah, Nurul; Hutomo, Muhammad Agita; Khoiru Nisa, Afifah; Ulfa, MH Muflihatul; Perdana Putri, Rachma Greta (Universitas Ahmad Dahlan, 2024)
Indonesia is an archipelagic country situated on the Ring of Fire, which frequently experiences earthquakes. Cilacap Regency is ranked 456th nationally with a medium-risk classification in the Earthquake Disaster Risk Index for the year 2021. The impact of earthquakes depends on their type and magnitude, including on schools, with 52,902 schools located in earthquake-prone areas. During the 2018 NTB Earthquake, 1,235 schools experienced damage. Earthquakes can also occur while children are studying at school. Elementary schools are one of the foundations of the children's community. The group of elementary school children is a vulnerable group that needs protection and, at the same time, needs to enhance their knowledge of earthquake disaster mitigation. One enjoyable medium to educate elementary school children about earthquake disaster mitigation is through comics.To determine the influence of Education with Comic Media on the Knowledge of Earthquake Disaster Mitigation for 4th-grade students at SD Islam Al-Azhar 16 Cilacap, a research was conducted using a qualitative research method with a Pre Experimental design using the One Group Pretest-Posttest design. The sampling technique used in this study was total sampling, so all 78 members of the population were included as samples.Statistical analysis using the Wilcoxon signed-rank test showed a Z-value of -6.941 and a significance value (p-value) of 0.000, at α = 0.05. This means that there is a significant difference in the average knowledge between before and after providing Education with Comic Media for Earthquake Disaster Mitigation.